Penerapan Metode Mind Mapping Untuk Meningkatkan Motivasi Belajar PAI Kelas V SDN 04 Padang Aro - Nur'adilah, Nur'adilah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Learning motivation is a crucial factor in improving the quality of education, particularly in Islamic Religious Education (PAI). However, PAI learning at SD Negeri 04 Padang Aro is still dominated by conventional lecture methods, which fail to engage students effectively. This study aims to examine the effectiveness of the Mind Mapping method in enhancing students' learning motivation on the topics of Faith in the Day of Judgment and Hajj and Qurban in Grade V. Mind Mapping is utilized to visualize religious concepts in an interactive graphic form, making the material easier to understand and increasing student participation. The research employs a descriptive approach through observation, interviews, and analysis of students' learning outcomes. The findings reveal that the application of Mind Mapping significantly improves students' learning motivation. Students become more active, creative, and better at retaining the material. This study contributes positively to the development of effective teaching methods to enhance the quality of PAI education in elementary schools.